Surrogate Parenting of the Black–tailed Jackrabbit (Lepus californicus) with Species Specific Considerations - Whitman, Regina (Wildlife Rehabilitation Bulletin, 2008)
This paper is offered as an alternative perspective to the recently published article Surrogate Parenting and Development Stages of Newborn Western Cottontails (Sylvilagus audubonii) and a Black–tailed Jackrabbit (Lepus californicus) Nursed by a Western Desert Cottontail (Thome and Scott 2006). The article suggests that captive care and release standards for black–tailed jackrabbits (jacks [Lepus californicus]) are the same as western desert cottontails (Sylvilagus audubonii) simply because a cottontail was the nursing surrogate to the jackrabbit. This article will provide previously published information on the importance of captive rearing of jackrabbits in accordance with their species specific needs and natural history, as well as reinforce the proper protocol for their rehabilitation.